Bone Marrow Stem Cells Anti-liver Fibrosis Potency: Inhibition of Hepatic Stellate Cells Activity and Extracellular Matrix Deposition - Sitanggang, Ervina Julien (Int J Stem Cells, 2017)
Transplantation of bone marrow derived stem cells (BMSCs) has been reported inhibits liver fibrosis. Several in vitro studies by co-culturing BMSCs and hepatic stellate cells (HSCs) indirectly or directly in 2D models showed inhibition of HSC as the key player in liver fibrosis. In this study, we investigated direct effect of BMSCs on HSCs by co-culturing BMSCs and HSCs in 3D model as it represents the liver microenvironment with intricate cell-cell and cell-matrix interactions. Primary isolated rat HSCs and BMSCs were directly co-cultured at 1:1 ratio with hanging drop method. The monoculture of rat HSCs served as positive control. Mono-culture and co-culture samples were harvested on day 3, 5 and 7 for histological analysis. The samples were analyzed for extracellular matrix deposition by Masson’s Trichrome staining, tenascin-C immunocytochemistry, resting HSC’s state as shown by positive Oil Red O stained cells. Our results indicated CD90(+)CD34(−) BMSCs anti-liver fibrosis potency as evidenced by higher proportion of Oil Red O-positive cells in the co-culture group compared to the monoculture group and the significant decrease in extracellular matrix deposition as well as the decrease in tenascin-C expression in the co-culture group (p<0.05) compared to the monoculture group. These findings demonstrate that BMSCs have a potential therapeutic effect against liver fibrotic process through their capacity to inhibit HSCs activation and their effect in minimizing extracellular matrix deposition.